Survival analysis on heart transplantation patients of different ages using Bayesian survival techniques - Raj, Jishnu; Roseline Mary, R . (International Journal of Engineering & Technology, 2019)
This study focuses to find the survival chances of the heart transplant patient using different survival analysis. The results are later compared with the survival analysis to check the accuracy. The age-based estimation of survival analysis is also performed. The research carried out using Bayesian Survival analysis with survregbayes, anovaDDP and Kaplan Meir methods for survival analysis. The obtained results have shown that, Bayesian survival analysis is more accurate than the normal survival analysis strategy. Based on variations in mismatched scores, the survival time fluctuates for different age groups. A plot for survregbayes model was generated for which, those below the age of 28 have higher chances of survival. The future enhancement would deploy a PH model for estimation than the currently used PO model. At the later stage the project also aims to find out the cause of hazard from an increased number of variables.Â Â Â